APLIKASI MONTESSORI DALAM PEMBELAJARAN MEMBACA, MENULIS DAN BERHITUNG TINGKAT PERMULAAN BAGI ANAK USIA DINI - Darnis, Syefriani (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
This paper was conducted to produce an effective learning model for developing literacy and numeracy in early childhood. Many teachers get locked out of the process of helping their students especially young learners to read , write and count because our education system is not allowed the young children is learned to do those activities at school. This really should not be so.Based on Dr.Maria Montessori who was a pioneer in teaching reading, writing and counting for young learners, the preparation for reading and writing begins long before formal school and teachers can do that at school as well as parents at home. The ability to read, write and count is not, in itself, a sufficient ambition. What is of supreme importance is bringing about, in a child, a desire to read , write, and count. In this paper we will find Montessori Activities which are the building literacy and numeracy skills. This activities is presented by using the well designed Montessori apparatus, reviewed and age appropriate for children.Key Word : Literacy and Numeracy, Montessori, Montessori Activities, Montessori Apparatus, Age Appropriate.